Highlights 2019 - Yearly status report EDEN Initiative - Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent (2019)
Almost exactly four years (March 2015 to May 2019) was the duration of the EDEN ISS project. Four years of intensive work, ups and downs - but all rewarded with the succesfull deployment of the research greenhouse in Antarctica. These four years pushed the EDEN group to a new level by establishing essential know-how, not only on a technical level also through the operational aspects of managing a multinational analogue mission with 15 partners from 8 countries. As the EDEN ISS container remains in Antarctica, the research and testing will continue. The year 2019 also marked an important year for the EDEN group by establishing its pathway to planetary system deployment. With the EDEN ISS NEXT design, the group established a first baseline design for future space greenhouse systems. Transferring space-rated systems to terrestrial applications was always one of the main goals of the EDEN group. With the new MEPA system and the upcoming development project, the group will design a rapid deployable food production system for crisis scenarios. The official grand opening of the educational Botanika exhibition was an important milestone for the public engagement activities of the EDEN group. The exhibit will remain a permanent part of the visitor center of the Botanika, establishing a useful communication tool for the coming years. The EDEN team looks confidently to the future as its development pathway for creating bioregenerative life support systems continues. The operation of the Antarctic research platform EDEN ISS will generate useful knowledge on the operational challenges of these systems.